Speech Acts Analysis and Its Application Within the Interlocutors’ Communication - Kamarudin Kamarudin (Cordova Journal : languages and culture studies, 2020)
This research deals with Speech Acts Analysis and Its Application Within the Interlocutors’ Communication which focused on its kinds, functions, and how each kind of illocutionary acts is performed by the students in FBMB Undikma under A Pragmatic Analysis. The kinds of speech acts; locutionary acts, illocutionary acts, and perlocutionary acts. The functions of illocutionary acts; representative, directive, commissive, expressive, and declarative. A descriptive qualitative method was employed since the data being analysed was in the form of descriptive data. Content analysis method was also employed due to get description of the research phenomena which in the forms of words, clauses, phrases, and sentences. There were twenty-four fragments being analysed. As the result, based on its classification, it showed that the most dominantly performed was locutionary acts 224 times, then followed by illocutionary acts 223 times, and the last one was perlocutionary acts 215 times. The declarative sentence had the highest frequency performed 131 times and in terms of the functions; representative had the highest frequency performed 163 times. It is found that representative was the highest frequency performed by the speakers as asserting, explaining, agreeing, suggesting, asking, reporting, informing, demanding, telling, claiming, affirming, denying, disbelieving, concluding, calling, answering, introducing, greeting, and clarifying.